Digital design and manufacturing technology : selected, peer reviewed papers from the conference on digital design and manufacturing, 26-28 April 2010, Hangzhou City, Zhejiang Province - Chai, Guozhong; Lu, Congda; Wen, Donghui (Advanced materials research ;, 2010)
During the past twenty years, digital design and manufacturing technology has become indispensable in many and various applications world-wide; involving many products and rapidly expanding markets. It has not only provided industry with new methods, tools and digitalized products - from design, materials processing to operating and management procedures - but is also changing the approaches, thinking patterns and working environments of people in the manufacturing field. The rapid growth of digital design and manufacturing processes has also brought with it some processing work-flow challenges. While the various resultant products provide an ideal solution for some processing steps, more dedicated and integrated systems are sometimes required. How best can one handle incoming data and orders, automate the design and perhaps engineering, make robust plans, manage the process and data and deliver quality goods. This special collection on digital design and manufacturing technology explains the ins and outs of CAD/CAM technologies, and how these tools can be used to model and manufacture building components and industrial design products. It offers a comprehensive overview of the field and expertly addresses a broad range of recent initiatives and other issues related to the design of parts and assemblies for manufacturing; including a broad range of software, numerically controlled machines, manufacturing processes and prototyping methods. This book will therefore provide a valuable and fruitful reference work for researchers in the field of digital design and manufacturing processes who wish to understand further the underlying mechanisms and create new and practical design technologies, systems and processes. It will also be particularly useful for practising engineers in digital design and manufacturing processing who are responsible for the design of efficient and effective operations. Selected peer-reviewed papers from an April 2010 conference are gathered in this two-volume set, offering an overview of the field of digital design and manufacturing technology. The papers describe software, computer numerical control machines, programming, manufacturing processes, and prototyping necessary for the design of parts for manufacturing and assembly. Major themes examined include computer-aided innovation based on TRIZ theory, inverse engineering in production development, computer numerical control, and machining technology and NC programming for complicated parts. Some specific topics examined include seismic response analysis of an adsorption tower based on ANSYS, a knowledge-based web service environment for 3D visualization, and a theoretical architecture for regional manufacturing systems. B & w photos and illustrations are included.